Strategic management in public procurement: The role of dynamic capabilities in equity and efficiency - Matilde Cappelletti; Leonardo M. Giuffrida; Sohvi Heaton; Donald S. Siegel (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
A key issue in strategic management in the public sector is how government creates economic and social value through procurement. Unfortunately, most procurement studies are based on contract theories, which fail to incorporate the growing role of strategic management in performance. We fill this gap by analyzing longitudinal data on contracting to assess the equity and efficiency effects of a form of affirmative action used by governments: set-aside programs. Employing a machine learning-augmented propensity score weighting approach, we find that set-aside contracts are negatively associated with contract performance. These effects are attenuated by an agency's dynamic capabilities and the extent to which the agency uses more competitive procedures. Our findings illustrate how the dynamic capabilities of a federal agency can simultaneously enhance equity and efficiency.
Keywords: D73; H57; O38; L22; 330; Dynamic capabilities; resource-based view; public procurement; machine learning; random forest